Quality of life in elderly patients with digestive tract cancers hospitalised at a general surgery department - Wysokiński, Mariusz; Fidecki, Wiesław; Korzeniowska, Monika; Wrońska, Irena (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2012)
Aim of the study : Although growing old is considered to be a physiological process, numerous pathological changes occur, which may cause cancers to develop, including digestive tract cancers. The aim of this work was to assess the quality of life in elderly patients with digestive tract cancers hospitalised at a general surgery department. Material and methods : The study involved the cohort of 103 elderly patients after surgical treatment of digestive tract cancers of various types. A diagnostic poll method based on a survey by questionnaire was employed in this work and the WHOQOL BREF scale was the research tool. Results : Investigated patients evaluated their general quality of life at a level of 3.05 and their general perception of health at a level of 2.56. Highest scores were obtained in the social scale – 13.61 and the environmental domain – 12.74. Physical and mental domains scored similarly, i.e. 11.94 and 12.05, respectively. The quality of life in the physical domain was higher among males. Investigated people with higher education enjoyed better quality of life than those with either secondary or elementary education. Conclusions: 1. Quality of life in elderly patients with cancers hospitalised at the general surgery department was on an average level. 2. General quality of life was statistically significantly better in investigated patients suffering from stomach cancer than in patients with diagnosed small intestine cancer, large intestine cancer, anus cancer, liver cancer, gall bladder cancer or pancreatic cancer.